The crisis of biomedical wastes associated with the COVID-19 pandemic and management using sustainable technologies for sound management of healthcare waste associated with pandemics - Sharma, Udbhav; Kalra, Shekhar; Gupta, Srishti; Seth, Nirali; Mawari, Govind; Kumar, Naresh; Daga, Mradul Kumar; Singh, M. Meghachandra; Joshi, Tushar Kant (International Journal Of Community Medicine And Public Health, 2022)
The outbreak of coronavirus disease 2019 (COVID-19) wreaked havoc all across the world, claiming numerous casualties. Managing the pandemic has resulted in the production of an unprecedented volume of biomedical waste (BMW), in the form of used personal protective equipment (PPE), diagnostic items, etc. It is a matter of utmost urgency that this BMW is treated, using newer and environmentally sustainable methods as compared to the available ones. The inadequacies of the conventional methods of bio medical waste management call for newer and sustainable alternatives for management like simple greenhouse containers, pyrolysis of polypropylene PPE, usage of silk masks, development of novel biodegradable masks, Antimicrobial Photodynamic therapy (aPDT), nano-photocatalysts, etc. These methods have numerous advantages over currently used methods like incineration, landfilling, etc., and can sustainably be used as an adjunct or an alternative to them.